A Bibliometric Analysis of Dropbox on Scopus Publication - Azmi N.N.; Hussain A. (Webology Center, 2023)
Having a considered that online storage and sharing has becoming an essential to organised, stay focused and get in sync contents for all team members to enlighten way to work. Dropbox is the world's first smart work space which bring content of all team members together whilst letting users use the tool they want. Dropbox was initiated in 2008. Based on the usefulness and benefits of Dropbox, there are many kinds of research has been conducted on this topic. Therefore, this paper aims to analyse the scientific literature and report various types of published documents related to the Dropbox based on the data obtained from the Scopus Database by using Perish software to combine the obtained data, VOS Viewer Software to visualize the obtained data and Microsoft Excel to analysis the obtained data analysis. As of 27thApril 2020, there are 506 documents were retrieved and analysed based on the key words' search result thru database. By using standard bibliometric indicators, this paper reports the documents types, source types, publication years, language of publications, subject area, most active source title, keywords, distribution of publications by countries, authorship, text analysis, most active institutions and citation analysis. As the result show that 1) 81% of the articles were published in conferences proceedings and journals articles. 2) 91% of the articles were published in English. 3) There is an increased growth rate of literature on Dropbox since 1985. However, the growth rate is slightly lower from 2016 until 2018. 4) Computer Science is the most popular subject category with respect to the frequency of citations, Halevi, Harnik, Pinkas and Shulman-Peleg (2011)'s article appears as the most cited paper with an average of 30.44 citations per year. 5) Keywords of the Digital Storage, Cloud Storages and Cloud Computing were the top three keywords used in the database which represented the main areas of about Dropbox. 6) An analysis by country, The United States (US) is first country published most articles about Dropbox with 138 (27.27%).Meanwhile, 6) a total of 446 (88.14%) articles were published as multi-authored with a mean index of 3.55 authors per paper. Therefore, this research reviews of Dropbox published articles and delivers details of growth of Drop box for these35 years. This may help in potential directions or reference for future research. 2021. All rights reserved.